Stent-Graft Deployment for Aortic Rupture after Stenting for Aortic Recoarctation - Alcibar, Juan (Texas Heart Institute, 2007)
We present the case of a 62-year-old woman who presented with recoarctation and then experienced rupture of the aorta and severe clinical deterioration after a stent was deployed. She was treated immediately by intrastent deployment of a stent-graft, which resolved the extremely serious situation.